2013
DOI: 10.1016/j.lfs.2012.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-dependent and receptor-independent endocannabinoid signaling: A therapeutic target for regulation of cancer growth

Abstract: The endocannabinoid system comprises the G-protein coupled CB1 cannabinoid receptor (CB1R) and CB2 cannabinoid receptor (CB2R), their endogenous ligands (endocannabinoids), and the enzymes responsible for their synthesis and catabolism. Recent works have revealed several important interactions between the endocannabinoid system and cancer. Moreover, it is now well established that synthetic small molecule cannabinoid receptor agonist acting on either CB1R or CB2R or both exert anti-cancer effects on a variety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 33 publications
(50 reference statements)
1
25
0
Order By: Relevance
“…Cell viability strongly depends on: (i) the 9 -THC concentration in contact with Caco-2 cells; (ii) the incubation time; and, (iii) the type of 9 -THC-based formulation (F = 26.647, p < 0.05, n = 140), which is in agreement with previously published investigations [4,23,51,52]. The factor of analysis of variance pointed out significant interactions of the 9 -THC concentration with the incubation time (p < 0.05) and with the type of 9 -THC-based formulation (p < 0.05).…”
Section: Cellular Toxicitysupporting
confidence: 90%
“…Cell viability strongly depends on: (i) the 9 -THC concentration in contact with Caco-2 cells; (ii) the incubation time; and, (iii) the type of 9 -THC-based formulation (F = 26.647, p < 0.05, n = 140), which is in agreement with previously published investigations [4,23,51,52]. The factor of analysis of variance pointed out significant interactions of the 9 -THC concentration with the incubation time (p < 0.05) and with the type of 9 -THC-based formulation (p < 0.05).…”
Section: Cellular Toxicitysupporting
confidence: 90%
“…A number of in vitro and murine models have shown that the CANNs CBD and THC can alter the way that tumour cells proliferate, as well as increase the capacity of these cells to undergo death by apoptosis and/or autophagy. These effects appear to be both dependent and independent of signalling via their cognate CBR (13,20). More recently, in the context of glioma, CANNs have also been shown to enhance the action of other treatment modalities such as chemotherapy and irradiation in vivo (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…The endocannabinoid system is thought to be important in the regulation of cancer cell apoptosis, proliferation, migration, adhesion and invasion. Increased expression of the cannabinoid receptors (CB1R and CB2R) and FAAH has been documented in prostate and breast cancer and has been associated with worse outcomes [31]. FAAH inhibitors are under development for the treatment of pain and inflammation [31], but may also be useful in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of the cannabinoid receptors (CB1R and CB2R) and FAAH has been documented in prostate and breast cancer and has been associated with worse outcomes [31]. FAAH inhibitors are under development for the treatment of pain and inflammation [31], but may also be useful in cancer. Our data suggests that FAAH inhibitors might be a potential targeted agent for obesity-driven cancers.…”
Section: Discussionmentioning
confidence: 99%